Protection of Electrical Networks - Preve Ch. Christophe (London, ISTE Ltd, 2006)
This book, designed for engineers, technicians, designers and operators working with electrical networks, contains theoretical and practical information on the design and set-up of protection systems. Protection of Electrical Networks first discusses network structures and grounding systems together with problems that can occur in networks. It goes on to cover current and voltage transformers, protection functions, circuit breakers and fuses. Practical explanations of how protection systems function are given, and these, together with tables of settings, make this book suitable for any reader, irrespective of their initial level of knowledge.